Hitting a triple in the non-alcoholic fatty liver disease field: sucrose intake in adulthood increases fat content in the female but not in the male rat offspring of dams fed a gestational low-protein diet. (18th December 2017) - Nicolás-Toledo, L.; Cervantes-Rodríguez, M.; Cuevas-Romero, E.; Corona-Quintanilla, D. L.; Pérez-Sánchez, E.; Zambrano, E.; Castelán, F.; Rodríguez-Antolín, J.
Abstract : The excessive consumption of carbohydrates is related to non-alcoholic fatty liver disease (NAFLD) in infants and adults. The effect of combining maternal malnutrition and a high carbohydrate intake on the development of NAFLD in adulthood remains unknown. We therefore hypothesized that consumption of 5% sucrose by the offspring of dams fed a low-protein diet during pregnancy promotes liver fat accumulation and oxidative damage differently in females and males. To test this, 12-month-old female and male offspring of mothers fed a Control (C) or low-protein diet (Restricted, R) were provided with either tap water or 5% sucrose for a period of 10 weeks. Livers were excised to measure the fat content and 3-nitrotyrosine (3-NTyr) immunostaining; serum samples were also obtained to measure the concentration of malondialdehyde (MDA). Data were analyzed using a non-repeated measures three-way analysis of variance to determine significant differences ( P <0.05) regarding to the interaction among maternal diet, sucrose consumption and sex. Results showed that the liver fat content of females from R mothers was higher than that of their male counterpart. Hepatic 3-NTyr immunostaining and serum MDA concentrations were not affected by the interaction involving maternal diet, sucrose consumption and sex. Otherwise, liver fat content was correlated with the hepatic 3-NTyr immunostaining and serum MDA concentrations only in females. Thus, sucrose intake in adulthood increases fat content in the female but not in the male rat offspring of dams fed with a low-protein diet during pregnancy. This research emphasizes the importance of a balanced diet during pregnancy and the influence of the diet on the adult offspring.